You can solve this in four steps: - Get x in terms of y (from the first equation). - Plug in for x in the second equation and solve for y. - Plug the value of y back into the x in terms of y, and find the value of x. - Plug into both original equations and double-check that the results make sense. Hope that helps :)
still confused. can you show me with this problem so i can work on the rest i have to do please
use elimination. 1(x-y=1) -1(x+y=3) 1x-1y= 1 -1x-1y=-3 ---------- -2y=-2 -- -- -2 -2 y=0 go back to the original problem now. x-y=1 x-0=1 1-0=1 x=1
Join our real-time social learning platform and learn together with your friends!